2013
DOI: 10.1177/2041731413505305
|View full text |Cite
|
Sign up to set email alerts
|

Process-induced extracellular matrix alterations affect the mechanisms of soft tissue repair and regeneration

Abstract: Extracellular matrices derived from animal tissues for human tissue repairs are processed by various methods of physical, chemical, or enzymatic decellularization, viral inactivation, and terminal sterilization. The mechanisms of action in tissue repair vary among bioscaffolds and are suggested to be associated with process-induced extracellular matrix modifications. We compared three non-cross-linked, commercially available extracellular matrix scaffolds (Strattice, Veritas, and XenMatrix), and correlated ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…(12) High-energy radiation as well can alter proteins directly by cleaving the protein chains, or indirectly by causing the buildup of free radicals in the surrounding atmosphere which themselves react with the protein groups and change protein structure. (4, 13, 14) Because some studies have shown a lesser reduction of the in vitro mechanical properties of ECM-derived scaffolds after electron beam sterilization when compared to gamma irradiation, electron beam radiation is generally the preferred irradiation method for ECM-derived devices. (15) Still, when comparing low temperature ethylene oxide with electron beam sterilization, the former seems to have a lesser effect on the in vitro mechanical properties and protein structure of dermal sheep collagen.…”
Section: Introductionmentioning
confidence: 99%
“…(12) High-energy radiation as well can alter proteins directly by cleaving the protein chains, or indirectly by causing the buildup of free radicals in the surrounding atmosphere which themselves react with the protein groups and change protein structure. (4, 13, 14) Because some studies have shown a lesser reduction of the in vitro mechanical properties of ECM-derived scaffolds after electron beam sterilization when compared to gamma irradiation, electron beam radiation is generally the preferred irradiation method for ECM-derived devices. (15) Still, when comparing low temperature ethylene oxide with electron beam sterilization, the former seems to have a lesser effect on the in vitro mechanical properties and protein structure of dermal sheep collagen.…”
Section: Introductionmentioning
confidence: 99%
“…Comparative studies of ADMs report differing biologic responses, ranging from mild‐to‐severe inflammation and scaffold remodeling to fibrous encapsulation . In one study comparing various human‐ and animal (porcine)‐derived ADMs, minimal neovascularization was noted at 20 weeks while rates of tissue ingrowth and tensile strength differed between ADM sources .…”
Section: Biologic Response To Other Materialsmentioning
confidence: 99%
“…32 While neovascularization was reported by the first assessment at 4 months with TIGR Matrix, 31 mild-to-moderate evidence of vascularization was observed by the first assessment at 6 weeks with P4HB as a mesh or plug. 32 Comparative studies of ADMs report differing biologic responses, ranging from mild-to-severe inflammation 33 and scaffold remodeling to fibrous encapsulation. 34 In one study comparing various human-and animal (porcine)-derived ADMs, minimal neovascularization was noted at 20 weeks while rates of tissue ingrowth and tensile strength differed between ADM sources.…”
Section: Biologic Response To Other Materialsmentioning
confidence: 99%
“…The presence of the α-Gal epitope on porcine tissues has been associated with rapid rejection. 68 The use of Strattice for repair of incisional hernias in Yucatan pigs compared to primary closure showed that primary closure caused more scarring and bone hyperplasia along the incision line. 67 In addition, glycosaminoglycans are still present, indicating that Strattice retains key markers for the presence of relevant biochemical components.…”
Section: Stratticementioning
confidence: 99%